INTEGRASI MEDIA ICT KE DALAM PENDEKATAN COLLABORATIVE LEARNING UNTUK MENINGKATKAN IKLIM KELAS DAN MOTIVASI BELAJAR BIOLOGI SISWA KELAS X-1 SMA BATIK 1 SURAKARTA - Febriyanti, Shelli; Prayitno, Baskoro Adi; Sugiharto, Bowo (Pendidikan Biologi, 2012)
ABSTRACT ? The  research is classroom action research. The aim is to improve class climate and student?s learning motivation in class X-1 of SMA Batik 1 Surakarta by integrating ICT media into collaborative learning approach  that implemented in biology learning  process.  This act is based on the biology learning process observation  in class X-1 where   researcher found some learning problems. They are class  climate  and  student?s  learning motivation. Based on literatures  study, we give solution to improve them by integrating ICT media into collaborative learning approach.  Main data  is  collected from questioner  and    observation. While additional data is taken from interview, documentation, and test. Validation data uses triangulation and expert team. The act of research consists  of two cycles. Research target is 65% for class climate and 60% for student?s learning  motivation. The result of cycle  1 describes that generally the research target is accomplished not optimally. Percentage of class climate is 65,54% and student?s learning motivation  is 72,58%. The result of cycle  2 describes that generally the research target is accomplished optimally.  Percentage of class  climate  is  73,65%  and  student?s learning motivation is 77,30%. This cycle stopped here because targets accomplished optimally. Class climate and student?s learning motivation increase well.  This learning approach can improve targets because it?s syntax  support student?s  interaction and  interest. The conclusion of this research describes that integration ICT media into collaborative learning approach can improve  class climate and student?s learning motivation in class X-1 of SMA Batik 1 Surakarta. Keywords:  ICT Media,  collaborative  learning,  class  climate,  student?s  learning motivation